THE INFLUENCE OF THE CONNECTING ORGANIZING REFLECTING EXTENDING (CORE) MODEL ON THE TEXT READING SKILLS OF STORY TEXT STUDENTS OF CLASS X SMAN 2 PAYAKUMBUH - Wangiman _; Neneng Wahyuni; Adi Warma; Hasnan _; Wirda Linda (Jurnal Ilmu Pendidikan Ahlussunnah, 2023)
This study aims todescribe the skills of reading saga texts using the Connecting, Organizing, Reflecting, Extending (CORE) learning model for Tenth grade students of Senior High School in Payakumbuh. Second, describing of reading saga text using the conventional model. Third,Determining the effect of using the Connecting, Organizing, Reflecting, Extending (CORE) learning model on reading skills of the tenth grade students of SMAN 2 Payakumbuh. The type of research is quantitative research with experimental methods. The populations are 205 students, and 40 students as sample was divided into two classes they are experimental and control class. The sampling method is using purposive sampling. Instrument is using multiple choice test. The results of the t-test (t-test) in the experimental class prove tcount with ttable (5,553>2,093), because tcount is greater than ttable then Ha (alternative hypothesis) is accepted. Furthermore, the results of the t-test (t-test) in the control class prove tcount with ttable (4,189>2,093), because tcount is greater than t〗_table, then Ha (alternative hypothesis) is accepted. The results of the t-test describe the results of the comparison of tcount with ttable (2,405>2,021), because tcount is greater than ttable, then Ha (alternative hypothesis) is accepted. The conclusion of this research is using the Connecting, Organizing, Reflecting, Extending (CORE) model is good for learning reading skills of saga texts for Tenth grade Senior High School students in Payakumbuh.